2009
DOI: 10.1308/003588409x359286
|View full text |Cite
|
Sign up to set email alerts
|

Undertaking Procedure-Based Assessment is Feasible in Clinical Practice

Abstract: PBAs are feasible in clinical practice and are valued by trainees as a means of enabling focused feedback and targeted training. Commitment from trainers and trainees will be required but, with adequate planning, the assessment tool is effective with minimal impact on clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 1 publication
1
36
0
1
Order By: Relevance
“…Triggered assessment may be more acceptable to clinical supervisors and trainees, as it involves less time and work. A recent study suggested that clinical supervisors can feasibly complete a PBA in the time available between operations on a theatre list, with median PBA completion and feedback times of 6-15 min 23 . The present results add support to the practical implementation of PBA in the operating theatre, with the mean time for PBA completion and feedback lasting 4·9 min.…”
Section: Discussionmentioning
confidence: 99%
“…Triggered assessment may be more acceptable to clinical supervisors and trainees, as it involves less time and work. A recent study suggested that clinical supervisors can feasibly complete a PBA in the time available between operations on a theatre list, with median PBA completion and feedback times of 6-15 min 23 . The present results add support to the practical implementation of PBA in the operating theatre, with the mean time for PBA completion and feedback lasting 4·9 min.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, a study published in 2009 on the feasibility of PBAs demonstrated that they are feasible in clinical practice when there is adequate planning and commitment from trainers and trainees. 7 This study looked at the time taken to complete PBA forms in the commonly performed colorectal procedures. The results were encouraging and most of the interviewees also felt that these assessments need adequate planning, enthusiasm and commitment.…”
Section: Discussionmentioning
confidence: 99%
“…4 At present, there are limited data on DOPS and PBA available in literature. [5][6][7] This is probably due to the fact that most of the assessment and direct observations are carried out informally. Several studies on workplace-based assessment have commenced since the introduction of the foundation programme and ISCP in the UK and therefore evidence regarding validity, reliability, feasibility and assessment quality should start to emerge soon.…”
Section: Ann R Coll Surg Englmentioning
confidence: 99%
“…A study in Bath suggested that weekly PBA is feasible and acceptable. 131 Although triggered assessments may be more acceptable to trainees and assessors as they involve less time and work, the philosophy of assessment for learning should be 'the more the better' because of the constructive feedback provided. Furthermore, early and frequent assessment must be encouraged in order to demonstrate a progression in surgical skills that should precede achievement of competence.…”
Section: Study Recruitment and Opportunities Lost For Workplace-basedmentioning
confidence: 99%